The quiet revolution the struggle for the rights of disabled Americans - Haskins, James 1941-2005; Stifle, J. M. (New York Thomas Y. Crowell, 1979)
Focuses on the human and civil rights the handicapped are campaigning for, and on the various methods they are using to bring change to society and make it more aware of the needs of the disabled.
"A John Day book."
Includes bibliographic references (pages 135-141) and index.
Keywords: People with disabilities -- Civil rights -- United States -- Juvenile literature; People with disabilities -- Civil rights